Performance Analysis of OFDM and OFDM-MIMO Systems under Fading Channels - Elsanousi, A.; Oztürk, S. (Engineering, Technology & Applied Science Research, 2018)
Fourth-generation (4G) wireless communication system is mainly based on MIMO (multiple input and multiple output) and OFDM (orthogonal frequency division multiplexing). The combination of these two techniques leads to a better system, known as OFDM-MIMO system, providing higher capacity and data rate. This paper demonstrates the BER (bit error rate) performance of OFDM and OFDM-MIMO system using convolution code to encrypt the data stream that can be sent over communication channels. Simulation is made on Matlab using three different channels (AWGN, Rician and Rayleigh). The simulation results show that the combined system has better performance compared to OFDM system. The practical part of this study was conducted by using two USRPs B210 (universal software radio peripheral) for transmitting and receiving, two antennas were used during transmission for both sides. The transmitted signal is successfully recovered.